articel EXPLORING THE INFLUENCE OF CORPORATE GOVERNANCE ON FINANCIAL REPORTING QUALITY AND INVESTOR CONFIDENCE - Mohamad Ruli Fahmi; Lili Adi Wibowo; Faisal Matriadi (PT. Kreatif Indonesia Satu, 2024)
Background Corporate governance has become increasingly critical in the wake of financial scandals and corporate collapses that have shaken global markets. As stakeholders demand greater transparency and accountability, the relationship between governance mechanisms, financial reporting quality, and investor confidence has garnered significant attention. Effective governance practices are essential to ensure accurate financial disclosures, maintain market stability, and foster trust among investors. Aims This study aims to explore the influence of corporate governance attributes—such as board independence, audit committee effectiveness, and CEO duality—on the quality of financial reporting and investor confidence. The research seeks to identify key governance practices that enhance transparency, reduce financial misstatements, and build sustainable investor trust across diverse regulatory and cultural environments. Research Method The study employs a mixed-methods approach, integrating quantitative and qualitative analyses. Quantitative data was collected from the financial and governance disclosures of 200 publicly listed companies across multiple industries between 2010 and 2020. Regression models were used to analyze the relationship between governance attributes and financial reporting quality. Qualitative data, derived from interviews with governance experts and financial analysts, was employed to contextualize the quantitative findings and provide deeper insights into governance practices. Results and Conclusion The findings reveal that robust corporate governance frameworks significantly improve financial reporting quality and enhance investor confidence. Board independence, frequent audit committee meetings, and the separation of CEO and chairman roles are identified as critical factors in reducing financial misstatements and fostering transparency. Comparative analysis highlights regional disparities in governance effectiveness, emphasizing the need for tailored governance reforms. Overall, the study underscores the importance of governance as a cornerstone of financial market stability and investor trust. Contribution This research contributes to the growing body of knowledge on corporate governance by providing empirical evidence on the governance-reporting-investor nexus. It offers actionable recommendations for policymakers, regulators, and companies to strengthen governance practices and promote financial transparency.